IMF Staff papers : Volume 41 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1994)
The paper presents a model of optimum currency areas using a general equilibrium approach with regionally differentiated goods. The choice of a currency union depends upon the size of the underlying disturbances, the correlation between these disturbances, the costs of transactions across currencies, factor mobility across regions, and the interrelationships between demand for different goods. It is found that, while a currency union can raise the welfare of the regions within the union, it unambiguously lowers welfare for those outside the union. [JEL F33, F36].